Pengaruh Lingkungan Kerja dan Stres Kerja Terhadap Kinerja Karyawan - Suwardi Gunawan; Muhamad Rasul Ibnu Nasir (Universitas Medan Area, 2023)
The purpose of this study was to examine and analyze the effect of the work environment and work stress on performance through job satisfaction as an intervening variable for employees at CV. Setia Abadi City of Samarinda. The research method used is explanatory research with a quantitative approach, namely statistical analysis with regression analysis and path analysis. Where before testing the hypothesis, instrument trials and classical assumption tests were first carried out. The sampling technique in this study was saturated sampling, where all members of the population were used as samples, namely 10 people. The research instrument used was a questionnaire regarding work environment, work stress, job satisfaction and employee performance. Based on the results of the calculations that have been done, it is concluded that the work environment variable has a positive and significant effect on employee performance at CV.Setia Abadi Kota Samarinda, then the work stress variable has a positive and significant effect on employee performance at CV. Setia Abadi Kota Samarinda, and work environment variables and work stress have a positive and significant effect on employee performance simultaneously on CV. Setia Abadi Kota Samarinda.